Anti-inflammatory and antinociceptive effects of Mitragyna speciosa Korth methanolic extract. - Shaik Mossadeq, Wan Mastura; Sulaiman, Mohd Roslan; Tengku Mohamad, Tengku Azam Shah; Chiong, Hoe Siong; Zakaria, Zainul Amiruddin; Jabit, Md Lip; Baharuldin, Mohamad Taufik Hidayat; Israf Ali, Daud Ahmad (Karger, 2009)
OBJECTIVES: To determine the anti-inflammatory and antinociceptive activities of Mitragyna speciosa Korth methanol extract in rodents. Materials and